Eksistensi Gay dan Peran Pendidik Kristen: Suatu Review Overview Kepustakaan - Asmat Purba; Juli Wahyu; Supriadi Agus; Martinus Laia; Bambang Triono (Tumou Tou, 2022)
Gay is generally used to refer to men with a same-sex or homosexual orientation. Gay is a disorder and a threat to the younger generation, so it should not be allowed to affect them as early as possible. Gay prevention can be done through Christian education in the family, church, and school. Today the existence of the gay community has spread throughout the world through social media. The purpose of this article is, first, to make the Christian congregation aware of the dangers of social media spreading gay influence in society. Second, urge Christian educators to educate about the impact of gayness and provide assistance to children at home, church, and school, so they are protected from gay influence. Students' curiosity is high enough to want to know everything they see on social media. Christian educators must be sensitive to sexual deviations that begin to appear when students experience puberty, start hanging out, and like the same sex. God strictly forbade Lot and his family to look back when God destroyed the immoral cities of Sodom and Gomorrah (Gen. 19:17). Christian educators are expected to be proactive in guiding students to immediately leave their sins so that God's wrath does not fall on them. This paper is based on a review overview of the literature, including the Bible, as an assignment for the course "Critical issues of education." The author examines the results of research and opinions in online newspapers, books, and journals published and refers to the Word of God.